Comparison of mosquito control programs in seven urban sites in Africa, the Middle East, and the Americas - Impoinvil, Daniel E. (2007)
Mosquito control programs at seven urban sites in Kenya, Egypt, Israel, Costa Rica, and Trinidad are described and compared. Site-specific urban and disease characteristics, organizational diagrams, and strengths, weaknesses, obstacles and threats (SWOT) analysis tools are used to provide a descriptive assessment of each mosquito control program, and provide a comparison of the factors affecting mosquito abatement. The information for SWOT analysis is collected from surveys, focus-group discussions, and personal communication. SWOT analysis identified various issues affecting the efficiency and sustainability of mosquito control operations. The main outcome of our work was the description and comparison of mosquito control operations within the context of each study site's biological, social, political, management, and economic conditions. The issues identified in this study ranged from lack of inter-sector collaboration to operational issues of mosquito control efforts. A lack of sustainable funding for mosquito control was a common problem for most sites. Many unique problems were also identified, which included lack of mosquito surveillance, lack of law enforcement, and negative consequences of human behavior. Identifying common virtues and shortcomings of mosquito control operations is useful in identifying “best practices” for mosquito control operations, thus leading to better control of mosquito biting and mosquito-borne disease transmission.